Retreatment with Bendamustine-Bortezomib-Dexamethasone in a Patient with Relapsed/Refractory Multiple Myeloma - Cerchione, Claudio; Nappi, Davide; Di Perna, Maria; Zacheo, Irene; Pareto, Anna Emanuele; Picardi, Marco; Catalano, Lucio; Pane, Fabrizio (Case Reports in Hematology, 2016)
The clinical management of relapsed/refractory multiple myeloma and the correct choice of the most suitable therapy in heavily pretreated and fragile patients are tough clinical issues for clinicians. In advanced phases of disease, the choice of available therapies becomes very poor, and the retreatment with previously adopted and effective therapy, although unpredictable, could be an effective option. In this report, we describe the clinical history of a patient, previously treated with 9 lines of therapy, refractory to bortezomib and IMIDs, for whom the retreatment with bendamustine resulted in a stable disease with good quality of life.